Projeto conceitual de uma planta de produção para fabricação de briquetes/pelets a partir de resíduos de carvão vegetal e serragem/maravalha de madeira - Batista, Jorge Luiz (2023)
With the imminent need to change the global energy matrix to a more sustainable model, alternatives to replace fossil fuels are necessary. With the increase in demand for fossil fuels, such as coal, oil and natural gas, which are responsible for a considerable amount of atmospheric emissions, mainly carbon dioxide, and still have limitations in their reserves and do not have the capacity for renewal. Therefore, fuels of plant origin that have the capacity to be renewable are important alternatives to replacing fossil fuels. Briquettes and pellets are fuels produced from wood biomass with high density and significant calorific value that can replace fossil fuels in many applications. The purpose of this work is the conceptual design of a pellet/briquette production plant that will process and densify sawdust/wood shavings and charcoal fines, forming a biofuel of high density and high calorific value, with high energy capacity. The equipment that produces pellets and briquettes processes a single type of raw material; this production plant has the advantage of processing more than one type of biofuel. The reference model by Rozenfeld et al. was adopted for development. (2006) and the selection of equipment to make up the production plant were chosen with the support of the multi-criteria method the Analytic Hierarchy Process (AHP), based on pre-defined choice criteria. As a result of the academic research process based on the multi-criteria method and the aforementioned reference model, a conceptual project was chosen for a plant for the production of pellets, consisting of storage in a suspended silo for sawdust and charcoal fines, a vibrating screen , ball mill, continuous rotary kiln, continuous rotary mixer, pneumatic control valve, wheel rotary system.